Management News and Notes (Academy of Management Journal, 1965)
The article presents an update on the Academy of Management and news related to business education in the U.S. as of September 1965. The Academy of Management Silver Anniversary Program will meet at the Warwick Hotel in New York City on December 27 to 29, 1965. The University of Southern California is planning a new organizational scheme for the Business School. Thomas H. Patten Jr. has been appointed Professor of Management at the University of Detroit.